File structures with Ada - Miller, Nancy E. (Redwood City, California : The Benjamin/Cummings Publishing Company, Inc., 1989)
This textbook meets the requirements of the Association for Computing Machinery's (ACM) course CS5 as defined in the ACM curriculum guidelines. The goal of this textbook is to study the external data structures necessary for implementing different file organization.
Chapter 1. Overview of files -- Chapter 2. ADA records and files -- Chapter 3. Blocking and buffering -- Chapter 4. Secondary storage devices -- Chapter 5. Sequential file organization -- Chapter 6. External sort/merge algorithms -- Chapter 7. Relative file organization -- Chapter 8. Search trees -- Chapter 9. Indexed sequential file organization -- Chapter 10. Multiple-key file organization.
Includes bibliographical references and index.
Keywords: ADA (COMPUTER PROGRAM LANGUAGE)